Has inflation targeting been successful? Evidence from unit root tests - Mesut Turkay; Burak Sencer Atasoy (Investigación Económica, 2019)
The popularity of inflation targeting has risen in the last decade and the number of countries that adopted inflation targeting as their monetary policy framework surpassed 40 by the end of 2016. This study analyzes whether inflation targeting around the world has been successful in terms of achieving the announced target and keeping inflation rate around it. We argue that a successful inflation targeting necessitates the deviation of inflation from the target be stationary. We employ both time series and panel unit root tests in order to analyze the stationarity properties of deviation of inflation from the target. Results of unit root tests provide evidence in favor of the success of inflation targeting framework around the world.
Keywords: C23; E52; E58; 330; Inflation targeting; central banks; inflation; unit roottests; stationarity; price stability